Novel fiber-reinforced polymer cross wrapping strengthening technique: A comparative study. Issue 5 (April 2020) - Zeng, Jun-Jie; Duan, Zhi-Jian; Guo, Yong-Chang; Xie, Zhi-Hong; Li, Li-Juan
This article presents a comparative study on behavior of fiber-reinforced polymer–confined concrete in axially loaded circular columns strengthened using three different fiber-reinforced polymer partial wrapping strengthening schemes: the fiber-reinforced polymer ring wrapping, the fiber-reinforced polymer strip helical wrapping, and the novel fiber-reinforced polymer strip cross helical wrapping. The test results show that at an identical confinement ratio, the strength enhancement efficiency of the fiber-reinforced polymer strip helical wrapping is slightly weaker than those of the other two strengthening schemes, while the strain enhancement efficiency of the fiber-reinforced polymer strip helical wrapping is the strongest among the three strengthening schemes. An analysis-oriented stress–strain model is proposed for the confined concrete with fiber-reinforced polymer partial wrapping, and the comparisons show that the model is capable to provide satisfactory predictions on stress–strain behavior of confined concrete with fiber-reinforced polymer partial wrapping.